2019
DOI: 10.3390/molecules24193554
|View full text |Cite
|
Sign up to set email alerts
|

A New Series of EDOT Based Co-Sensitizers for Enhanced Efficiency of Cocktail DSSC: A Comparative Study of Two Different Anchoring Groups

Abstract: Herein, we report the design and synthesis strategy of a new class of five EDOT based co-sensitizers (CSGR1-5) by introducing different donors (2,3,4-trimethoxypheny, 2,4-dibutoxyphenyl, and 2,4-difluorophenyl) and anchoring groups (rhodamine-3-acetic acid and cyanoacetic acid) systematically. The synthesized metal-free organic co-sensitizers were employed for cocktail dye-sensitized solar cells along with N749 (black dye). The DSSC devices with a mixture of co-sensitizers (CSGR1-5) and N749 have shown a 7.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…The long alkyl chain of JH-1 inhibited electron recombination, and the complementary spectral response in the co-sensitized device affected the efficiency of the entire device [ 10 ]. A positive effect of co-sensitization has been also demonstrated for DSSC systems in which one of the dyes was based on ruthenium [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The advantages of co-sensitization, such as improvement of optical absorption, IPCE response, electron lifetime, dye regeneration, dye coverage and cell preparation cost, have been demonstrated for DSSC cells sensitized with the dyes of the structures D-A-π-A and π-A in combination with a copper-based electrolyte [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The long alkyl chain of JH-1 inhibited electron recombination, and the complementary spectral response in the co-sensitized device affected the efficiency of the entire device [ 10 ]. A positive effect of co-sensitization has been also demonstrated for DSSC systems in which one of the dyes was based on ruthenium [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The advantages of co-sensitization, such as improvement of optical absorption, IPCE response, electron lifetime, dye regeneration, dye coverage and cell preparation cost, have been demonstrated for DSSC cells sensitized with the dyes of the structures D-A-π-A and π-A in combination with a copper-based electrolyte [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The large or midfrequency region signies the recombination resistance (R 2 ) at the working electrode of the TiO 2 /dye/electrolyte interface. 27,46 The third semicircle (low-frequency range) indicates the series resistance (R 1 ) of platinum and FTO glass. The obtained recombination resistance values (R 2 ) of the DSSCs sensitized In fact, the higher the R 2 value, the lower the charge recombination rate between the conduction band of the TiO 2 semiconductor and the electrolyte.…”
Section: Electrochemical Impedance Study Of the Dsscsmentioning
confidence: 99%
“…The improved V OC observed for the co-sensitized DSSC devices can be attributed to the lower rate of recombination between the injected electrons in the TiO 2 semiconductor conduction band and the redox electrolyte (I 3 À /I À ). Owing to their small size, the co-sensitizers provide better surface coverage 27,45 by adsorbing into the pores and gaps in the TiO 2 , whereas the steric hindrance of the bulky ruthenium-based dye molecule prevents its adsorption. From the results, the lower efficiency of IMA5 when co-sensitized with IMA1 (h ¼ 5.44%) and IMA4 (h ¼ 5.83%) compared to when cosensitized with IMA2 (h ¼ 6.25%) and IMA3 (h ¼ 6.19%) can be attributed to the breaking of the continuous conjugation by the pyrazole moiety in IMA1 and by the thiazole moiety in the case of IMA4, which would prevent efficient electron injection into the conduction band of TiO 2 .…”
Section: Photovoltaic Characterization Of Dsscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zolkepli et al (2015) showed that the 1:4 mixture of Tradescantia spathacia and Ixora coccinea pigments had the highest cell efficiency (= 0.80%). Koyyada et al (2019) systematically introduced alternative donors and anchoring groups, and we created a new class of five EDOT-based co-sensitizers with N749 (black dye). The power conversion efficiency (PCE) of DSSC devices with a mixture of co-sensitizers and N749 was the maximum, which was higher than the PCE of a single N749 dye (6.18%).…”
Section: Introductionmentioning
confidence: 99%